A new converged Emperor Penguin Optimizer for biding strategy in a day-ahead deregulated market clearing price: A case study in China. (15th July 2021) - Lu, Xiaohui; Yang, Yang; Wang, Peifang; Fan, Yiming; Yu, Fangzhong; Zafetti, Nicholas
Abstract-: In this research, a new approach has been suggested for providing an optimization bidding strategy in the day-ahead market for case research in China. This research uses a newly developed version of Emperor Penguin Optimizer (CEPO) to govern the fitness function of all individuals based on the Market Clearing Price (MCP) probability function. The resemblance amounts between each day and the next day are used for clustering. The clustering is performed based on the well-known subtractive clustering methodology. A simulation model using the probability function in MCP estimates the fitness function of the generated strategies. The results indicate that this method proposed is a statistically effective bidding design in China's day-ahead market related to two other plans from the literature. Highlights: An optimized method for bidding strategy in the day-ahead market in China. Converged Emperor Penguin Optimizer (CEPO) for problem optimization. The problem is to minimize the Market Clearing Price (MCP) probability function. Subtractive clustering for data clustering between each day and the next day.